2021
DOI: 10.1016/j.amepre.2021.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Indoor Air Laws for Onsite Cannabis Consumption Businesses in the U.S.

Abstract: Introduction: Secondhand cannabis smoke, like secondhand tobacco smoke, creates unhealthy indoor air quality. Ventilation and engineering techniques cannot reduce this pollution to healthy levels, and complete smoke-free policies are the only way to provide healthy indoor environments. Even so, multiple state and local governments have begun to allow indoor smoking of cannabis in businesses.Methods: A systematic search of Lexis Advance, NewsBank, and government websites for U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…249 Cannabis companies stated that youth prevention programming helped prevent preteen cannabis use 220 , 221 without messaging against consumption and promoted recycling while avoiding occupational risks arising from workplace exposure to toxins 250 , 251 and secondhand smoke exposure where cannabis is consumed. 252 , 253 Prevention programming directed at youths by the tobacco industry was historically less effective than government prevention programming and promoted youth consumption via forbidden fruit messaging. 28 , 29 In the US, youths had a 12.8% rate of current cannabis use compared with 15.4% rate of electronic cigarette use and a 3.3% rate of combustible cigarette use in January through June 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…249 Cannabis companies stated that youth prevention programming helped prevent preteen cannabis use 220 , 221 without messaging against consumption and promoted recycling while avoiding occupational risks arising from workplace exposure to toxins 250 , 251 and secondhand smoke exposure where cannabis is consumed. 252 , 253 Prevention programming directed at youths by the tobacco industry was historically less effective than government prevention programming and promoted youth consumption via forbidden fruit messaging. 28 , 29 In the US, youths had a 12.8% rate of current cannabis use compared with 15.4% rate of electronic cigarette use and a 3.3% rate of combustible cigarette use in January through June 2021.…”
Section: Discussionmentioning
confidence: 99%
“…The tobacco industry has used youth prevention, marketing, and environmental CSR programs to displace effective educational programs and regulation . Cannabis companies stated that youth prevention programming helped prevent preteen cannabis use without messaging against consumption and promoted recycling while avoiding occupational risks arising from workplace exposure to toxins and secondhand smoke exposure where cannabis is consumed . Prevention programming directed at youths by the tobacco industry was historically less effective than government prevention programming and promoted youth consumption via forbidden fruit messaging .…”
Section: Discussionmentioning
confidence: 99%
“…Municipal regulations can impact consumption levels by way of location and physical accessibility of cannabis products for both current and potential consumers. According to previous literature reviews and document syntheses, increased accessibility has been associated with higher consumption levels of alcohol, tobacco, and cannabis in studies at the municipal/local, provincial/state and national levels (Henriksen, 2012;Rotering et al, 2021;Stockwell et al, 2019). Incidentally, the most recent Statistics Canada report showed that, since enactment of cannabis legalization, self-reported cannabis use in the last three months increased in the three provinces considered between the first quarter of 2018 to the last quarter of 2020: from 16.6% to 21.7% in Alberta; from 13.5% to 23.1% in Ontario and; from 10.4% to 10.6% in Québec (Rotermann, 2021).…”
Section: Physical Accessibilitymentioning
confidence: 98%
“…(20,26,27) Additionally, multiple states have legalized or decriminalized cannabis and within these states retail outlets selling cannabis have proliferated, with some allowing on-site consumption, and use of cannabis in public spaces is becoming common. (28)(29)(30)(31) These economic and policy initiatives are likely to increase the number of pedestrians under the influence of alcohol and at risk of falls and injuries from motor vehicles. (12,20,32,33) To support advances in polices and urban design strategies to prevent pedestrian falls, there is a need for data describing the burden of alcohol and drug-related injurious falls (6).…”
Section: Introductionmentioning
confidence: 99%